Feynman - Ottaviani, Jim (First Second, 2011)
In this substantial graphic novel biography, First Second presents the larger-than-life exploits of Nobel-winning quantum physicist, adventurer, musician, world-class raconteur, and one of the greatest minds of the twentieth century: Richard Feynman. Written by nonfiction comics mainstay Jim Ottaviani and brilliantly illustrated by First Second author Leland Myrick, Feynman tells the story of the great man's life from his childhood in Long Island to his work on the Manhattan Project and the Challenger disaster. Ottaviani tackles the bad with the good, leaving the reader delighted by Feynman's exuberant life and staggered at the loss humanity suffered with his death" -- from publisher's web site.